Dynamic marketing capability as mediator between resources and SMEs performance - Kusyana, Dewa Nyoman Benni; Giantari, I Gusti Ayu Ketut; Sukaatmadja, I Putu Gde; Ekawati, Ni Wayan (Edelweiss Applied Science and Technology, 2025)
This research investigates the effect of entrepreneruial orientation (EO) and knowledge management (KM) on business performance, directly and mediated by dynamic marketing capability (DMC). This study involved 235 SME entrepreneurs in the fashion sector in Bali Province. The respondents were given a questionnaire consisting of 47 statement items. Model and hypothesis testing was carried out using PLS-SEM. The research results show that the direct relationship between EO, KM, DMC, and BP is positive and significant. Further, it was found that DMC consisting of proactive market orientation and value innovation mediate the influence of entrepreneruial orientation and knowledge management on business performance. The mediation test results show that value innovation consistently plays a more significant role in mediating than proactive market orientation.. Theoretically, this research contributes to the theoretical framework by introducing DMC as a mediating variable under the dynamic capability view. Apart from that, this research contributes theoretically by proving that RBV is still relevant today and is needed to launch company capabilities. This research provides a practical contribution to SMEs, namely the importance of acting dynamically by reconfiguring resources to face changes in the business environment.